Structural and geometric left ventricular remodeling and systolo-diastolic parameters of intracardiac hemodynamics in isolated obesity - S. Yu. Dashutina; S. Yu. Peretolchina; S. S. Barats; V. A. Serebrennikov (Российский кардиологический журнал, 2005)
In obese patients without cardiovascular comorbidity, structural, morphometric, geometric, and systolo-diastolic parameters, as well as variants of structural and geometric left ventricular (LV) remodeling were analyzed. The mechanisms of change for left heart chambers' geometry in obesity are universal for all known processes affecting intracardiac hemodynamics. Therefore, obesity can be regarded as a universal pathologic process, affecting cardiac geometry.